B42 Huntington Disease and Olfactory Dysfunction: Structural Abnormalities of the Olfactory System and Early Caspase Activation in the Olfactory Bulb are Observed in HD Mouse Models. (17th September 2014) - Laroche, M; Demers, MJ; Lessard-Beaudoin, M; Garcia-Miralles, M; Kreidy, C; Franciosi, S; Hayden, MR; Pouladi, MA; Graham, RK
Abstract : Olfactory dysfunction and altered neurogenesis are observed in several neurodegenerative disorders including Huntington disease (HD). These deficits are an early symptom and correlate with decline in global cognitive performance, depression and degeneration of olfactory regions in the brain. The olfactory dysfunction observed in neurodegenerative diseases is often accompanied by structural abnormalities of the olfactory epithelium, the olfactory bulb (OB) and the olfactory cortices in human brain. Despite evidence demonstrating olfactory dysfunction in HD patients, only limited details are available in murine models. Preliminary data demonstrate a decrease in OB weight (YAC128, p = 0.027; BACHD, p = 0.023) and the volume of the piriform cortex (YAC128, p = 0.004; BACHD, p = 0.013) is observed in HD vs. WT mice. Furthermore, a decrease in piriform neuronal counts (p = 0.003) and enhanced immunostaining of EM48 is observed in the olfactory regions of YAC128 vs. WT brain. We also examined odour investigation behaviours in the mice using the habituation/dishabituation test. YAC128 mice investigate trial 1 odours longer than WT littermates (p = 0.04). In order to determine whether apoptotic events are associated with the olfactory dysfunction and altered neurogenesis in HD we are assessing caspase activation and TUNEL. Preliminary data demonstrate that a significant decrease in the proform of caspase-6, suggesting activation, and an increase in levels of the proform of caspase-8 are observed in pre-symptomatic YAC128 OB vs. WT. No change in caspase-3 or -9 was detected. Identification of early markers of the disease will help inform therapeutic approaches for HD and will clarify the utility of olfactory function tests in HD patients.